2001
DOI: 10.1007/s007020170083
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stimulating protease-activated receptor-1 and -2 in A172 human glioblastoma

Abstract: Human glioblastoma cell line A172 expressed protease-activated receptor-1 and -2 (PAR-1 and PAR-2). We investigated the effects of the stimulation of these receptors by receptor-activating agonist peptides on the Ca2+ signaling, protein kinase C translocation, cell morphology and cell proliferation in A172. Both PAR-1 agonist SFLLRN and PAR-2 agonist SLIGKV induced an increase in [Ca2+]i. The prior treatment of A172 with PAR-2 agonist SLIGKV did not influence the [Ca2+]i response to PAR-1 agonist SFLLRN or thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 49 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…The result of the literature review is summarized in Tables 1, 2, 3, and 4, (Arora et al 2008;Beaulieu and Church 2007;Bromberg et al 2001;Caruso et al 2006;Cooper et al 2003;Elzer et al 2008;Fujimoto et al 2006;Ghio et al 2006;Granovsky-Grisaru et al 2006;Hazarika et al 2004;Hjortoe et al 2004;Ikeda et al 2003Ikeda et al , 2006Jahan et al 2007;Jin et al 2003;Kang et al 2003;Kaufmann et al 1998Kaufmann et al , 1999Kaufmann et al , 2000Kim et al 2002;Massi et al 2005;Matej et al 2007;Miyata et al 2000;Mize et al 2008;Ohta et al 2003;Okamoto et al 2001;Radjabi et al 2008;Rudroff et al 2002;Sánchez-Hernández et al 2008;Seo et al 2007;Shibata et al 2004;Yoshii et al 2005;Zhang et al 2004). …”
Section: Resultsmentioning
confidence: 96%
“…The result of the literature review is summarized in Tables 1, 2, 3, and 4, (Arora et al 2008;Beaulieu and Church 2007;Bromberg et al 2001;Caruso et al 2006;Cooper et al 2003;Elzer et al 2008;Fujimoto et al 2006;Ghio et al 2006;Granovsky-Grisaru et al 2006;Hazarika et al 2004;Hjortoe et al 2004;Ikeda et al 2003Ikeda et al , 2006Jahan et al 2007;Jin et al 2003;Kang et al 2003;Kaufmann et al 1998Kaufmann et al , 1999Kaufmann et al , 2000Kim et al 2002;Massi et al 2005;Matej et al 2007;Miyata et al 2000;Mize et al 2008;Ohta et al 2003;Okamoto et al 2001;Radjabi et al 2008;Rudroff et al 2002;Sánchez-Hernández et al 2008;Seo et al 2007;Shibata et al 2004;Yoshii et al 2005;Zhang et al 2004). …”
Section: Resultsmentioning
confidence: 96%
“…Thus, as mentioned above, uncoupling of PAR-1 to the MAP kinase cascade in DLD-1 cells may be the main reason for the lack of growth promotion mediated by PAR-1. In the previous study, we found that PAR-2 stimulation inhibited the proliferation of A172, a human glioblastoma cell line (25). Recent studies demonstrated that PAR-2 activating peptide and trypsin induced the proliferation of pancreatic cancer cells through the stimulation of MAP kinase (26,27).…”
Section: Cell Proliferation and Pars In Other Cellsmentioning
confidence: 89%
“…After SDS-PAGE, the proteins were transferred onto the nitrocellulose membranes and were blotted with antibodies against PAR-2 (Santa Cruz Biotechnology), MEK, MAP kinase, and their phosphorylated forms (Cell Signaling Technology, Beverly, MA, USA). The reaction was developed as described previously (9,16).…”
Section: Immunoblottingmentioning
confidence: 99%